RELEVANSI KISAH POTRE KONENG DENGAN SITI MARYAM DALAM AL-QUR’AN - Moh. Ainul Yaqin; Abd. Basid; Masykur Arif (Program Studi Ilmu Al-Qur’an dan Tafsir, Fakultas Ushuluddin, Universitas Annuqayah (UA), 2024)
There is a similarity between the story of Potre Koneng in the Madura legend with the story of Siti Maryam either in the personality or with the peculiarity of both. The most visible thing in both stories is that they gave birth to a baby without any sexual relations or marriage; therefore, the relevancy of these two stories is attractive to discuss. This research aims to answer three questions. First, how was the story of Potre koneng? Second, how was the story of Siti Maryam in al-Quran? Third, does the story of Potre Koneng have relevance to the story of Siti Maryam in al-Quran? The method or approach used in this research is non-interactive qualitative, focusing on concept analysis. While analytical technique in this research is documentation. The relevancy of these two stories is in the personality of both: obedient devotees. Siti Maryam was a woman who loved to worship Allah, accordingly, she was willing not to live with her family and to decide to leave for Mihrab to be close to God. In addition, Potre Koneng was a woman who was diligent in performing religious service. She preferred to meditate in Payudan cave than to marry. Furthermore, Potre koneng and Siti Maryam were pregnant without any sexual relations or marriage. What was different was the pregnancy process. Potre Koneng was pregnant by way of dreaming of having sexual relations with Adipoday when meditating in the cave of Payudan. Besides, Siti Maryam underwent the pregnancy by spirit blowing with the angel Gabriel mediator.